The Elements and Color of Lacustrine Record Revealed Lake Environmental Changes in Semiarid Northern China: A Case Study From Chagan Nur Lake of Southern Mongolian Plateau - Wang, Zhong; Li, Guoqiang; Wang, Xiaoyan; Gou, Siyi; Deng, Yanqing; Tao, Shuxian; Zhang, Yunian; Yang, He; Zhao, Wenwei; Jin, Ming (Frontiers in Earth Science, 2021)
The lakes at southern Mongolian Plateau are sensitive to the variations of EASM during Holocene, and hence the lacustrine records of these lakes provide prospects for understanding how lake environments respond to EASM changes at different timescales. The interpretation of proxy indexes of lacustrine sediments is complex due to the various climatic or/and environmental factors influencing the processes during deposition and after deposition. In this study, the elements and color of an 11.7 m lacustrine record from Chagan Nur at the southern Mongolian Plateau of northern China were analyzed to constrain the lake environmental changes during the Holocene. The results show that stable elements of Al, Si, K, Ti, Fe, Rb are more related to surface erosion or/and vegetation coverage, and the variations of Sr are related to lake level changes in Chagan Nur. The elements and color of the lacustrine record show that a small and shallow lake condition occurred at Chagan Nur during 11.7-10.5 ka, the lake level increased during 10.5-7 ka, and then the lake shrank with strengthed surface erosion during 7-6.2 ka and from 2 ka to the present. The lake level and surface erosion changes of Chagan Nur have shown a direct response to EASM precipitation changes reconstructed from the pollen record from the Chagan Nur lake and other records from northern China.